2021
DOI: 10.1111/nmo.14130
|View full text |Cite
|
Sign up to set email alerts
|

Altered interaction between enteric glial cells and mast cells in the colon of women with irritable bowel syndrome

Abstract: Background: Enteric glial cells (EGC) and mast cells (MC) are intimately associated with gastrointestinal physiological functions. We aimed to investigate EGC-MC interaction in irritable bowel syndrome (IBS), a gut-brain disorder linked to increased intestinal permeability, and MC.Methods: Parallel approaches were used to quantify EGC markers in colonic biopsies from healthy controls (HC) and patients with IBS. Data were correlated with MC, vasoactive intestinal polypeptide (VIP) and VIP receptors (VPAC1/VPAC2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Meira de-Faria et al [21] 2020 Casecontrol Investigate the interaction between EGC and mast cells in IBS and how a gut-brain disorder is linked with increased intestinal permeability and mast cell activation.…”
Section: Study Design Aim Of Study Conclusionmentioning
confidence: 99%
“…Meira de-Faria et al [21] 2020 Casecontrol Investigate the interaction between EGC and mast cells in IBS and how a gut-brain disorder is linked with increased intestinal permeability and mast cell activation.…”
Section: Study Design Aim Of Study Conclusionmentioning
confidence: 99%
“…49 Besides neurons, enteric glial cells are a second important cell type of the enteric nervous system and are involved in the modulation of neuronal function, but also in epithelial barrier function. 50 Activation of enteric glial cells (ie, gliosis) was shown in FD 49 and IBS, 51 although an earlier study found decreased glial cell responses during Ca 2+ imaging on exposure to IBS-D supernatant which was dependent on activation of the histamine receptor 1 (H1R). 52 Clearly, as noted above, submucosal enteric neurons are not transmitting nociceptive information to the central nervous system.…”
Section: Recent Advances In Clinical Practicementioning
confidence: 99%
“… 119 Studies on IBS colonic mucosa showed increased GFAP expression, indicating an enteric glial activation that was correlated negatively with MC density, suggesting altered EGC-MC interactions. 120 Inflammation, even if mild, leads to persistent GI nerve changes, and these inflammation-induced changes persist after recovery. These changes could affect structural morphology (nerve bundles, hypertrophy, and/or hyperplasia) and neurotransmitter expression or receptor, such as a decreased release of acetylcholine and increased secretion of 5-hydroxytryptamine.…”
Section: Mast Cells and Functional Diseasesmentioning
confidence: 99%